THE IMPLICATIONS OF THE IAIN MADURA DIGITAL LIBRARY ON IMPROVING STUDENTS DIGITAL QUOTIENT SKILL - Ardiansyah Ardiansyah; Mutik Nur Fadhilah; Zalinawati Binti Haji Mohaimin; Desintha Dwi Rosyadi Putri (JURNAL KOULUTUS, 2024)
The era of digital industry 4.0 and society 5.0 has led to digitalization in various aspects oflife. One of them is the existence of a digital library at IAIN Madura which makes it easy forthe academic community to access information. Especially for PGMI Study Program studentsin increasing digital quotient. The purpose of this study was to analyze the implications ofthe digital library of IAIN Madura in increasing the digital quotient of PGMI Study Programstudents. The research method is qualitative, through a descriptive approach. The datacollection was obtained through observation, interviews and documentation. The subjects ofthis study were 150 students of the PGMI Study Program. The results of this study indicatethat the implications of the digital library of IAIN Madura in increasing the digital quotientof PGMI Study Program students are developing cognitive abilities, digital skills, emotionalintelligence, digital literacy and social skills.Keywords: Digital Library, Digital Quotient.